Electrocatalytic Oxidation of Benzaldehyde Oxime Using Potassium Perchlorate in Biphasic Medium. (2017) - Joy, Biju; Balaganesh, M.; Joseph Selvaraj, S.
Abstract: Benzaldehyde oxime can be readily converted to the corresponding benzaldehyde in high yields. The electrochemical oxidation was optimized with various experimental parameters to result in the high yield of benzaldehyde (80%). The reaction was carried out with platinum electrodes at room temperature in an undivided cell within constant biphasic medium consisting of chloroform containing benzaldehyde oxime and an aqueous solution of potassium perchlorate as a mediator with a stoichiometric amount of H2 SO4 .